2018
DOI: 10.3390/coatings8100337
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Characteristics of PEDOT:PSS Coated on Glass and Plastics by Ultrasonic Substrate Vibration Post Treatment

Abstract: In this work, we excited as-spun wet films of PEDOT:PSS by ultrasonic vibration with varying frequency and power. This is a low-cost and facile technique for tailoring the structural and surface characteristics of solution-processed thin films and coatings. We deposited the coatings on both rigid and flexible substrates and performed various characterization techniques, such as atomic force microscopy (AFM), scanning electronic microscopy (SEM), X-ray photoelectron spectroscopy (XPS), attenuated total reflecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 60 publications
4
15
0
Order By: Relevance
“…Although at this high frequency the amplitude of vibration was small, i.e. ∼0.5 nm (Gholampour et al 2018), this experimental observation is in qualitative agreement with the theoretical work of Shklyaev, Alabuzhev & Khenner (2009), who suggested that film stability could be achieved for very-high-frequency ultrasonic horizontal vibrations.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Although at this high frequency the amplitude of vibration was small, i.e. ∼0.5 nm (Gholampour et al 2018), this experimental observation is in qualitative agreement with the theoretical work of Shklyaev, Alabuzhev & Khenner (2009), who suggested that film stability could be achieved for very-high-frequency ultrasonic horizontal vibrations.…”
Section: Resultssupporting
confidence: 90%
“…However, at this frequency, we can clearly see that the intensity of the waves (even for the regions where it is the highest) is lower than the intensity of the 20 and 40 kHz cases. This gradual decrease in the wave amplitude with increasing excitation frequency and then the complete disappearance of waves at f = 170 kHz agree with the fact that the amplitude of excitation decreases with frequency (Gholampour et al 2018).…”
Section: Ultrasonic Vibrationssupporting
confidence: 84%
See 2 more Smart Citations
“…The RMS roughness of the 800 DPI Ag coated substrate is measured by laser interference and is 6 AE 1 nm. It is slightly larger than that of PET/ITO found in the literature (3.32 AE 0.53 nm) 61 and similar to those of other printed Ag layers. 24 The roughness and the sheet resistance are low enough to build efficient OLEDs on top of the ink-jet printed Ag.…”
Section: Ink-jet Printed Bottom Electrodesupporting
confidence: 84%